Minors in the Mines: Archaeological Indicators of Child Labor in Prehistoric Mining Contexts in Europe - (:unkn) unknown (My University, 2019)
Developing a theoretical and methodological framework for the study of children, childhood, and child labor in prehistory has two goals. The first is to reintegrate children into cultural narratives in light of the increased popularity of the topic among archaeologists; the second is to equip researchers with the tools to apply developing theories to prehistoric populations in which there is material and physical evidence of child labor. Using the prehistoric mining complex of Hallstatt in alpine Austria as a case study, this thesis highlights how a reevaluation of existing data can provide a more inclusive interpretation of childhood even in the distant past. By viewing the existing material and biological evidence through the theoretical lens of Grete Lillehammer’s child’s world, and incorporating additional lines of evidence through analogy, a child-centric analysis can be generated. Future directions for the study of children and childhood in prehistoric mining contexts are discussed in the course of demonstrating the unique opportunity these communities provide to discuss childhood in occupationally specialized societies.
Keywords: Childhood; Hallstatt; Mining; Prehistory